MANEJO DA IRRIGAÇÃO E ABUBAÇÃO NITROGENADA NO FEIJOEIRO CULTIVAR BRS FC 402 - MEDEIROS, Rosevaldo Domingos; LOPES, Adriano da Silva; Kraeski, Marcos Jefferson; FRANCO, Jhonatan da Silva; MACIEL, Gustavo de França (ANAIS DO ENIC, 2023)
-